The Effect of Servant Leadership and Self-Efficacy on Performance Through Organizational Citizenship Behavior (OCB) on The Elders and Deacents of The GPM Classis in Ambon City - Nelson Edward Ajawaila; Novalien Carolina Lewaherilla; Gerrit M Pentury (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
This study aims to analyze the influence of Servant Leadership and Self-Efficacy on Performance through Organizational Citizenship Behavior (OCB) in Elders and Deacons throughout the GPM Classis in Ambon City. This study uses a quantitative approach with a survey method. The study population was the Elders and Deacons throughout the GPM Classis in Ambon City, totaling 781 people, with a basic population for determining the sample of 225 people from four representative congregations (Bethel, Diakonos, Syaloom, and Pniel). Determination of the number of samples used the Slovin formula with a 10% error rate, resulting in a sample of 69 respondents. Data collection was carried out through a questionnaire measured using a Likert scale. Data analysis used the Structural Equation Modeling (SEM) method based on Partial Least Square (PLS) with the help of SmartPLS software version 4 to test direct and indirect relationships between variables. The results of the study indicate that Self-Efficacy has a positive and significant effect on Performance, Organizational Citizenship Behavior (OCB) has a positive and significant effect on Performance, and Servant Leadership has a positive and significant effect on OCB. Conversely, Servant Leadership does not have a significant effect on Performance, and Self-Efficacy does not have a significant effect on OCB. The results of the mediation test indicate that OCB is able to fully mediate the effect of Servant Leadership on Performance, but is unable to mediate the effect of Self-Efficacy on Performance. This finding emphasizes the importance of strengthening service-oriented leadership through the formation of OCB behavior, as well as increasing the Self-Efficacy of Elders and Deacons to support the continuous improvement of service performance throughout the GPM Class of Ambon City.